The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1002/j.1460-2075.1994.tb06530.x
|View full text |Cite
|
Sign up to set email alerts
|

The 5′ end of yeast 5.8S rRNA is generated by exonucleases from an upstream cleavage site.

Abstract: We have developed techniques for the detailed analysis of cis-acting sequences in the pre-rRNA of Saccharomyces cerevisiae and used these to study the processing of internal transcribed spacer 1 (ITS1) leading to the synthesis of 5.8S rRNA. As is the case for many eukaryotes, the 5' end of yeast 5.8S rRNA is heterogeneous; we designate the major, short form 5.8S(S), and the minor form (which is seven or eight nucleotides longer) 5.8S(L). These RNAs do not have a precursor/product relationship, but result from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
325
4
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(355 citation statements)
references
References 51 publications
18
325
4
2
Order By: Relevance
“…Effect of the bipartite allele on pre-rRNA processing+ Strains BMA41 (WT [lanes 1 to 3]) and YCJL7 (RRP5-N2 ϩ RRP5-C1 [lanes 4 to 6]) were grown in glucose-rich medium at 30 8C (lanes 1 and 4) or shifted at 37 8C during 8 h or 16 h (lanes 2 and 5 or 3 and 6, respectively)+ Total RNA was extracted and subjected to Northern analyses+ About 10 mg of total RNAs were loaded in each lane+ The panels represent consecutive hybridizations of the same membrane with the different probes drawn in Figure 1A+ Fig+ 4B,C, lanes 4 to 6) although 32S accumulation appears nearly equivalent at both temperatures (Fig+ 4B-F, lanes 4 to 6)+ This could either suggest that the direct cleavage of the 32S pre-rRNA at site A 3 might be a temperature-sensitive event or that the 21S species is unstable at 37 8C+ We favor the latter hypothesis since the direct cleavage of 32S species at site A 3 also produces the 27SA 3 species (Fig+ 1C) whose specific derivative product 5+8S S rRNA accumulates normally (Fig+ 5A; see below)+ The 21S pre-rRNA was first reported as accumulating in a yeast strain deleted for the snoRNA snR10 (Tollervey, 1987;see Fig+ 1B) and was also detected in three rrp5 mutant strains, but not in the Rrp5p-depleted strain (Venema & Tollervey, 1996)+ The fact that the RRP5 bipartite-allele-expressing strain does not contain detectable 20S precursor but does contain mature 18S rRNA strongly suggests that the aberrant 21S species can be used as a precursor for 18S synthesis and that this 21S pre-rRNA can be cleaved at site D (Fig+ 1C)+ There is a modest accumulation of the 35S rRNA in the mutant YCJL7 strain (Fig+ 4B-G) indicating that the early cleavages at sites A 0 and A 1 are weakly affected+ Nevertheless, the excised A 0 A 1 fragment accumulates at a wild-type level as shown in Figure 5B, thus indicating that the cleavages occur in the YCJL7 strain+ Furthermore, hybridization with probe in 59 ETS failed to reveal any accumulation of 33S pre-rRNA species (Fig+ 4G)+ While the 27SB pre-rRNAs were found to be strongly reduced in a Rrp5p-depleted strain (Venema & Tollervey, 1996), these species accumulate near a wild-type level in the bipartite-allele-containing strain (Fig+ 4E,F)+ Consistently, the mature 25S and 5+8S derivative products were normally detected in that strain (Fig+ 4A and Fig+ 5A)+ The apparent lower level of 27SB and 25S rRNAs detected at 37 8C (Fig+ 4A and 4E-F, lanes 5 and 6) is rather because of a lower loading of the corresponding lanes than to a real accumulation defect+ Moreover, the two forms of 5+8S rRNA, the major short form (5+8S S ) and the minor long form (5+8S L ; see Henry et al+, 1994), were both detected at normal levels in YCJL7 strain (Fig+ 5A) and wild-type reported ratios ranging from 1:7 to 1:10 (5+8S L :5+8S S ) were determined by densitometry analyses (Eichler & Craig, 1994;Allmang et al+, 1996) + Venema & Tollervey (1996) have shown that the Rrp5p-depleted strain strongly underaccumulated the major short form 5+8S S rRNA due to an inhibition of the A 3 cleavage in that strain+ No such defect was observed in the YCJL7 strain which is consistent with an efficient cleavage event occurring at site A 3 + We conclude that despite its unusual genetic organization the so-call...…”
Section: Rrp5 Overexpression Modifies Mitochondrial Importmentioning
confidence: 86%
See 1 more Smart Citation
“…Effect of the bipartite allele on pre-rRNA processing+ Strains BMA41 (WT [lanes 1 to 3]) and YCJL7 (RRP5-N2 ϩ RRP5-C1 [lanes 4 to 6]) were grown in glucose-rich medium at 30 8C (lanes 1 and 4) or shifted at 37 8C during 8 h or 16 h (lanes 2 and 5 or 3 and 6, respectively)+ Total RNA was extracted and subjected to Northern analyses+ About 10 mg of total RNAs were loaded in each lane+ The panels represent consecutive hybridizations of the same membrane with the different probes drawn in Figure 1A+ Fig+ 4B,C, lanes 4 to 6) although 32S accumulation appears nearly equivalent at both temperatures (Fig+ 4B-F, lanes 4 to 6)+ This could either suggest that the direct cleavage of the 32S pre-rRNA at site A 3 might be a temperature-sensitive event or that the 21S species is unstable at 37 8C+ We favor the latter hypothesis since the direct cleavage of 32S species at site A 3 also produces the 27SA 3 species (Fig+ 1C) whose specific derivative product 5+8S S rRNA accumulates normally (Fig+ 5A; see below)+ The 21S pre-rRNA was first reported as accumulating in a yeast strain deleted for the snoRNA snR10 (Tollervey, 1987;see Fig+ 1B) and was also detected in three rrp5 mutant strains, but not in the Rrp5p-depleted strain (Venema & Tollervey, 1996)+ The fact that the RRP5 bipartite-allele-expressing strain does not contain detectable 20S precursor but does contain mature 18S rRNA strongly suggests that the aberrant 21S species can be used as a precursor for 18S synthesis and that this 21S pre-rRNA can be cleaved at site D (Fig+ 1C)+ There is a modest accumulation of the 35S rRNA in the mutant YCJL7 strain (Fig+ 4B-G) indicating that the early cleavages at sites A 0 and A 1 are weakly affected+ Nevertheless, the excised A 0 A 1 fragment accumulates at a wild-type level as shown in Figure 5B, thus indicating that the cleavages occur in the YCJL7 strain+ Furthermore, hybridization with probe in 59 ETS failed to reveal any accumulation of 33S pre-rRNA species (Fig+ 4G)+ While the 27SB pre-rRNAs were found to be strongly reduced in a Rrp5p-depleted strain (Venema & Tollervey, 1996), these species accumulate near a wild-type level in the bipartite-allele-containing strain (Fig+ 4E,F)+ Consistently, the mature 25S and 5+8S derivative products were normally detected in that strain (Fig+ 4A and Fig+ 5A)+ The apparent lower level of 27SB and 25S rRNAs detected at 37 8C (Fig+ 4A and 4E-F, lanes 5 and 6) is rather because of a lower loading of the corresponding lanes than to a real accumulation defect+ Moreover, the two forms of 5+8S rRNA, the major short form (5+8S S ) and the minor long form (5+8S L ; see Henry et al+, 1994), were both detected at normal levels in YCJL7 strain (Fig+ 5A) and wild-type reported ratios ranging from 1:7 to 1:10 (5+8S L :5+8S S ) were determined by densitometry analyses (Eichler & Craig, 1994;Allmang et al+, 1996) + Venema & Tollervey (1996) have shown that the Rrp5p-depleted strain strongly underaccumulated the major short form 5+8S S rRNA due to an inhibition of the A 3 cleavage in that strain+ No such defect was observed in the YCJL7 strain which is consistent with an efficient cleavage event occurring at site A 3 + We conclude that despite its unusual genetic organization the so-call...…”
Section: Rrp5 Overexpression Modifies Mitochondrial Importmentioning
confidence: 86%
“…The early pre-rRNA cleavages at sites A 0 , A 1 , and A 2 are known to be required for the synthesis of 18S rRNA (Venema & Tollervey, 1995) whereas cleavage at site A 3 is required for the normal formation of 5+8S rRNA (Henry et al+, 1994) + Venema & Tollervey (1996) have recently demonstrated that Rrp5p is the first rRNA-processing component required for both snoRNP-dependent cleavages A 0 /A 1 /A 2 and RNase MRP cleavage A 3 (see Fig+ 1B)+ This was shown by genetic depletion of Rrp5p, which results in a synthesis defect of both 18S and 5+8S rRNAs+ We show here that two conditional alleles of RRP5 cause a defect only in 18S rRNA formation without altering the 5+8S rRNA synthesis+ These results indicate that the Rrp5p functions in 18S and 5+8S rRNA-processing can be separated+ It also suggest that our modified forms of Rrp5p could be affected for relationship with the snoRNP complex while putative functions within the RNase MRP complex could take place normally+…”
Section: S and 58s Rrna-processing Functions Of Rrp5p Can Be Separmentioning
confidence: 99%
“…RNase MRP (mitochondrial RNA processing) was first identified as a ribonucleoprotein enzyme capable of in vitro formation of primers for mitochondrial DNA replication (Chang & Clayton, 1987;Schmitt & Clayton, 1992;)+ However, most of the enzyme is localized to the nucleolus (Reddy et al+, 1981;Reimer et al+, 1988;Kiss & Filipowicz, 1992), with only minute amounts found in the mitochondria (Topper et al+, 1992;Li et al+, 1994)+ Its cellular location suggested that the primary function of RNase MRP is in ribosome biogenesis+ Indeed, recent genetic evidence has established that RNase MRP is required for normal processing of 5+8S rRNA in Saccharomyces cerevisiae (Schmitt & Clayton, 1993b;Chu et al+, 1994;Lygerou et al+, 1994Lygerou et al+, , 1996+ The 5+8S rRNA of S. cerevisiae exists in short (5+8S S ) and long (5+8S L ) versions, differing by 6-7 nt at their 59 ends (Rubin, 1974;Lindahl et al+, 1992)+ The ratio of 5+8S S :5+8S L in wild-type cells is 5-10:1+ However, a single base change in the RNA subunit of RNase MRP results in a substantially decreased ratio of 5+8S S to 5+8S L , as well as accumulation of a very long version of 5+8S rRNA with 149 bases of the ITS1 sequence attached at the 59 end (Shuai & Warner, 1991;Lindahl et al+, 1992;Chu et al+, 1994)+ These observations together with other experiments (Henry et al+, 1994) have led to the conclusion that RNase MRP is responsible for initiating the processing of the short form of 5+8S rRNA by cleaving the pre-rRNA in the transcribed spacer between the 18S and 5+8S moieties+ RNase MRP is structurally related to RNase P, the endonucleolytic enzyme that creates the mature 59 end of tRNAs+ Both enzymes have one RNA subunit (here called MRP RNA and P RNA) that share secondarystructure features (Forster & Altman, 1990;Schmitt & Clayton, 1993a)+ Furthermore, RNases MRP and P of S. cerevisiae contain eight common protein subunits (Lygerou et al+, 1994;Chu et al+, 1997;Dichtl & Tollervey, 1997;Stolc & Altman, 1997;Chamberlain et al+, 1998;Stolc et al+, 1998); only one protein specific to each of the two nucleases has been identified (Schmitt & Clayton, 1994;…”
Section: Introductionmentioning
confidence: 85%
“…Secondary structure of a portion of the 59 half of the large subunit rRNA+ Shown is the entire sequence of 5+8S rRNA in bold type, with 59 and 39 ends indicated+ The ITS2 proximal stem is indicated and is formed by the base pairing of sequences near the 39 end of 5+8S with those near the 59 end of 25S+ The ITS2 sequence, represented here by dashed lines, is 234 nt in yeast and joins the 39 end of 5+8S and the 59 end of 25S in pre-rRNA+ For a schematic of the predicted ITS2 structure, see Figure 6B+ The sequence of the unique tag (shown in italics; after Musters et al+, 1989) and the structural alterations induced in that stem by the presence of the tag inserted into the KpnI site is shown below+ Structure is modeled after that proposed by Gutell et al+ (1993)+ tional for RNA polymerase I activity+ Transcription of the plasmid-borne rDNA gene is driven by Pol II and is repressed by growth in glucose and induced in response to galactose+ The Pol II transcripts from this construct are processed accurately and efficiently and incorporated into ribosomes which are fully functional (Nogi et al+, 1991a,b;Henry et al+, 1994)+ The yeast strain (NOY504) used in these experiments carries a disruption in the rrn4 (rpa12) gene encoding a Pol I subunit (A12+2) (Nogi et al+, 1993), which renders this strain temperature sensitive for Pol I transcription and cell growth+ Use of this strain has two advantages+ First, processing of plasmid-encoded rRNA transcripts can be studied under conditions of reduced competition with endogenous, chromosomal rDNA transcripts+ Second, the ability of mutated rDNA genes to support processing, ribosome assembly, and translational function can be readily tested by their ability to confer galactose-dependent growth at a restrictive temperature (37 8C) (Nogi et al+, 1991a,b;Henry et al+, 1994)+ A third component of the system used here was a unique; 18-base-tag sequence inserted within the mature 25S coding sequence (Musters et al+, 1989;Beltrame & Tollervey, 1992) for use in Northern analyses and primer extensions+ The sequence of the tag is indicated in Figure 2 and the insertion site is depicted schematically in Figure 3A+ Although it had been shown previously that the tag inserted at this site had no effect on processing or translational function (Musters et al+, 1989), we have analyzed tagged and untagged versions of each of the mutations described below+ The results were identical for the two versions and only the results for tagged constructs are presented below+ This system was used to directly test the proposed requirement for the 5+8S:25S interaction in the ITS2-proximal stem+ This was carried out by constructing single and compensatory double-clustered mutations in the plasmid-encoded yeast rDNA template (pNOY102) as outlined in Figure 3A+ Sequences for each of the mu-FIGURE 3. Mutagenesis of yeast rDNA template+ A: Schematic showing the mutagenesis strategy+ Using PCR directed mutagenesis (as described in Materials and Methods) with yeast rDNA plasmid pNOY102 as the template, four constructs wer...…”
Section: Mutagenesis Of Rdna Templatesmentioning
confidence: 99%
“…Pre-rRNA processing scheme in yeast+ Schematic of the genomic organization of rDNA and processing pathways of the pre-rRNA transcript+ The full-length precursor in yeast, 35S, is processed by alternative coexisting pathways, utilizing a variety of processing sites (denoted by gray letters and thin arrowheads on the precursor, 35S)+ Some of the first cleavages separate 18S rRNA from the 5+8S/25S+ Subsequent cleavages within ITS2 yield mature 5+8S and 25S and are shown by the heavy lines with arrows+ The sequence and structural requirements for these ITS2 processing events are focused upon in this work+ ITS: Internal Transcribed Spacer+ ITS2-proximal stem, a near perfect 15-base-pair helix in Xenopus, is the longest of the 3 base paired interactions between 5+8S and 28S+ This model for U8 snoRNA function and the role of the ITS2-proximal stem is based on four lines of evidence+ First, extensive mutagenesis studies and phylogenetic conservation of regions within the U8 sequence implicate the 59 end of U8 in critical sequence-dependent interactions (Peculis & Steitz, 1994;Peculis, 1997b)+ Second, 29-O-methyl oligoribonucleotides complementary to the 59 end of U8 RNA inhibit processing of the large subunit rRNAs in Xenopus oocytes (Peculis, 1997b)+ This inhibition is sequence specific, does not result in degradation of U8 RNP and can be rescued by subsequent injection of U8 snoRNA+ Thus, inhibition in this oligonucleotide competition experiment is presumably because of interference with base pairing of the 59 end of U8 RNA to its target+ Third, complementarity between the 59 end of U8 RNA and the 59 end of 28S rRNA is phylogenetically conserved, implicating this segment of 28S rRNA as a potential U8 target site (Peculis, 1997b)+ Fourth, 29-O-methyl oligoribonucleotides complementary to the 5+8S or 28S rRNA sequences in the ITS2-proximal stem inhibit processing of the large subunit rRNAs (Peculis, 1997b)+ While this fourth result is consistent with a requirement for the ITS2-proximal stem in processing, a direct test of this key feature of the model was lacking+ To provide such a test, we have taken advantage of the observation that this stable, base paired structure involving 28S and 5+8S rRNA is conserved in mature ribosomes across evolution (see Figs+ 2 and 6A)+ Thus, this interaction also occurs in yeast pre-rRNA, for which a genetic system to analyze mutations affecting rRNA processing is readily available (Nogi et al+, 1991a,b;Henry et al+, 1994)+ The results of our analyses in yeast demonstrate that the structure of the ITS2-proximal stem is essential for processing, whereas the sequence of the stem affects efficiency+…”
Section: Introductionmentioning
confidence: 99%